If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -10 = 4(x + 0) Reorder the terms: -10 + y = 4(x + 0) Reorder the terms: -10 + y = 4(0 + x) Remove the zero: -10 + y = 4(x) Solving -10 + y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + y = 10 + 4x Combine like terms: -10 + 10 = 0 0 + y = 10 + 4x y = 10 + 4x Simplifying y = 10 + 4x
| 12(2x-1)=3(8x+5) | | 7+2y-4=9y+48-2y | | 12x+3=x-5 | | 6x^2-2x+9=0 | | Y-13=-10(x-7) | | 0.28571428571428571428571428571429*x=10 | | .75x+.125(x-5)=.75 | | y-35=3(x-5) | | 4.5q-2.6-4.1q=-0.6-1.7 | | 2.3x+4.5=0.3-.5x | | .66(4x-1)=-22 | | 5x+40=2x+4 | | 8p+5=13+7p | | (4x-5)-(8x-6)= | | 10x+16=-(x+17) | | 3(y^2-2)= | | y-60=4(x-10) | | 7[9-7(8-x)-9]=9[7(9x-8)+6]-82 | | 660x(1-6x)=0 | | 330x(1-6x)=0 | | 4x-12=90+4x | | .5x+.1=.7x-.3 | | 750x(1-15x)=0 | | 28r+42-7(5r+9)= | | x-30=16 | | f/3-(f-6/6)=7/6 | | -(2X+3)+6x= | | 3x+2.5=6x-2 | | .6(15y+10)-3(4y+6)=0 | | 2x+11=x+3 | | x+16=4x+7 | | 6x-1=2x+27 |